Male Outmigration and Women's Work and Empowerment in Agriculture : The Case of Nepal and Senegal - World Bank Group; Food and Agriculture Organization of the United Nations (World Bank, Washington, DC, 2018)
The objective of this study is to examine the linkages between migration and women’s work and empowerment in agriculture in Nepal and Senegal. In particular, this analysis seeks to understand: (i) how outmigration influences women’s work in agriculture; (ii) the consequences of male-dominated migration on gender roles and women’s empowerment; and (iii) whether and how outmigration impacts household food security.